PENINGKATAN PEMAHAMAN KONSEP IPAS MELALUI MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA POKATA SISWA KELAS V SD - Rahmadani, Zulfa Arifia; Ismaya, Erik Aditia; Ermawati, Diana (Universitas Islam Malang, 2025)
This research aims to increase the understanding of science and science concepts for class V students through the problem based learning model assisted by POKATA media. POKATA media is an acronym for smart card posters that can be used to help implement science learning on changes that occur on Earth. The method used was classroom action research carried out at SD Negeri 3 Kalipucangkulon with 25 class V students as the subject, consisting of 13 male students and 12 female students. The research took place in 2 cycles with 2 meetings in each cycle, there were stages of planning, implementation, observation and reflection. Data collection techniques include observation, tests, interviews and documentation. Data analysis techniques include qualitative and quantitative data analysis. Indicators of understanding the IPAS concept are restating the concept, giving examples, classifying, concluding, comparing and explaining. The results of the research show that there is an increase in the ability to understand science and science concepts for fifth grade students at SD Negeri 3 Kalipucangkulon through the problem based learning model assisted by POKATA media. This can be seen in the number of students who completed cycle I as many as 12 students with a percentage of 48% and the number of students who completed cycle II as many as 20 students with a percentage of 80%. The application of the problem based learning model assisted by POKATA media can improve the ability to understand science and science concepts by achieving predetermined success indicators.Keywords: POKATA media, problem-based learning, understanding of IPAS concepts